Modelling and Simulation of Surface Diffusion in Heterogeneous Porous Materials - Sean P. Rigby (Surfaces, 2025)
The surface diffusion flux is known to dominate mass transport within many amorphous porous materials, used as adsorbents, heterogeneous catalysts, and membranes, employed in many chemical processes. However, while the impact of surface coverage has been widely studied and reviewed, relatively little attention has been paid to the impact of surface geometric and energetic heterogeneity on the surface diffusion rate, which would inform intelligent materials selection. It was, thence, the aim of this work to survey studies of the impact of surface structure on surface diffusion. Since the so-called “maximally realistic” modelling approach is found to be infeasible, due to limitations on the degree of structural characterisation possible for complex disordered surfaces, and the level of detail and length scales it is possible to represent with current computing power, a range of alternative approaches have been adopted. It has been seen that the Galilean idealisation of atomistic models has rendered them sufficiently tractable in order to study the impact of certain surface features, such as traps or ruts, on surface diffusion. Theoretical justifications have been used to develop minimalist models of amorphous surfaces, and mass transport thereon, that do selectively include the key surface parameters, and have, therefore, been successfully empirically validated for a range of different surfaces and adsorbate types.